Ceramide is involved in triggering of cardiomyocyte apoptosis induced by ischemia and reperfusion. - Bielawska, A. E. (1997)
Involvement of ceramide signaling in the initiation of apoptosis induction in myocardial cells by in vitro and in vivo ischemia and reperfusion was analyzed. Synthetic cell permeable C2-ceramide induced apoptotic death of rat neonatal cardiomyocytes in vitro. In vitro ischemia (oxygen/serum/glucose deprivation) led to a progressive accumulation of ceramide in cardiomyocytes. After 16 hours of simulated in vitro reperfusion (readdition of oxygen, serum and glucose), the level of ceramide in surviving cells was found to have returned to baseline, whereas, levels in nonadherent dead cells remained high. In the rat heart left coronary artery occlusion model, ischemia with the subsequent reperfusion, but not ischemia alone, induced apoptosis in myocardial cells as demonstrated by DNA electrophoresis and measurement of soluble chromatin degradation products. The content of ceramide in ischemic area was elevated to 155% baseline levels at 30 minutes, and to 330% after 210 minutes of ischemia. Ischemia (30 minutes) followed by reperfusion (180 minutes) increased the ceramide level to 250% in the ischemic area. The combination of results obtained in both in vitro and animal models demonstrate for the first time that ceramide signaling can be involved in ischemia/reperfusion death of myocardial cells.